Foliage houseplant responses to low formaldehyde levels. (January 2019) - Panyametheekul, Sirima; Rattanapun, Thanakorn; Morris, John; Ongwandee, Maneerat
Abstract: House plants are reported to 'clean' formaldehyde from indoor environments and thus reduce its deleterious health effects. We measured formaldehyde removal rates at concentrations similar to those caused by new furniture or office photocopiers. We also measured CO2 and humidity changes, counted the stomata density and monitored leaf color and shape changes. Controls were an artificial polyester "fern" and methanol as the VOC. All plants reduced formaldehyde from 0.75 ppm to below 0.2 ppm in six hours.. The plants fall into two major groups with different responses: one group showed high removal rates: Boston fern (0.85 m h −1 ), golden pothos (0.41 m h −1 ), Spanish moss (0.44 m h −1 ) and spider plant (0.40 m h −1 ) - faster than the artificial fern (0.09 m h −1 ). They also show no change in color and appear to completely assimilate formaldehyde. Another group absorbed formaldehyde at a significantly lower rate (dumb cane: 0.07 m h −1 ; aloe vera: 0.17 m h −1 ; and Chinese evergreen: 0.09 m h −1 ) and had a generally different overall behavior from the 'fast' group - different CO2, humidity and variance changes - suggesting a different formaldehyde absorption mechanism. An 'intermediate case', snake plant (0.29 m h −1 ), has a slower rate than the fast group but also exhibited other changes, suggesting some combination of both mechanisms. Overall good correlations between formaldehyde uptake rates and stomata counts, total leaf area and water evapotranspiration rates were shown by all these plants. Highlights: Measurements of formaldehyde absorption, stomata counts, evapotranspiration, CO2 production, hue and size changes. Correlations of formaldehyde uptake rates with stomata density and leaf area. Separation of foliage house plants into two groups in response to formaldehyde.